Gastroenterology - Heuman, Douglas M. (W. B. Saunders Co., 1997)
Virginia Commonwealth University, Richmond. Introductory overview of gastrointestinal diseases for students. Covers anatomy and physiology, disease processes, and clinical aspects of diagnosis and therapy. Includes review questions. Illustrated. Softcover. DNLM: Digestive System Diseases.